Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Anak Balita di Wilayah Kerja Puskesmas Nulle Timor Tengah Selatan Nusa Tenggara Timur - Gde Aldy Kurnia Griayasa; Dewa Ayu Putu Ratna Juwita; Komang Triyani Kartinawati (Aesculapius Medical Journal, 2024)
Stunting or too short in stature is defined as a height of less than -2 SD (Standard Deviation) below the WHO growth standard median. This study aims to explain the factors that influence the incidence of stunting in children aged 2-5 years at the Nulle Community Health Center, South Central Timor District, NTT. This research is a quantitative analytic study with a case control approach design, which uses 100 samples, consisting of 50 cases and 50 controls. Sampling using consecutive sampling technique. Data collection was carried out by measuring height, interviews and filling out questionnaires. The collected data is analyzed univariately, bivariately and multivariately using the SPSS 24.0 for windows program. Based on the Chi-Square test, a significant relationship was found between feeding pattern (p-value 0.00), parental education level (p-value 0.02), history of infection (p-value 0.04) and premature birth (p-value 0.00). Meanwhile, the variables of exclusive breastfeeding, mother's height, utilization of health services, distance between pregnancies, sanitation and water supply have no significant relationship. This study shows inappropriate feeding pattern in toddlers is the most determinant factors influencing stunting compared to other risk factors (odds ration = 7,32). Further research is needed with a mixed methods approach in order to obtain more comprehensive, valid, reliable and objective. results to further analyse the risk factors of stunting.